Perbedaan Prestasi Belajar Dan Kesegaran Jasmani Pada Anak Sekolah Dasar Stunting Dan Non Stunting Di Kecamatan Kartasura Kabupaten Sukoharjo - KARTIKASARI, Dewi, Siti Zulaekah, A., M.Si, Ahmad Farudin, SKM, M.Si (2015)
Background: Stunting is linear growth disarders caused by chronic malnutrition, which is expressed by the value of the z-score of height by age (TB/U) <- 2 standar deviaci (SD). Stunting is a nutritional problem which has the largest proportion compared with other nutritional problems. Nearly 90 % of stunting children lives in developing countries, the prevalence of stunting in Asia by 36 %. Objective: This study aims to determine the differences between the learning achievement and physical fitness in elementary school children stunted and nonstunted in Kartasura District Sukoharjo. Research Methods: This is an observational study with cross sectional approach. This research subject is elementary school children aged 9-13 years old who attend school in the area Kartasura Sukoharjo 413 children. The sample is 70 subjects which is divided into 2 groups with a random sampling technique. The research data collection is using documentation. The technique data analysis is using Independent sample t - test. Results of the Research : The results of different test Independent sample t-test differences in learning obtained with a significance level (p - value) of 0.021, the result of defferent between learning achievement of elementary school children stunting and non stunting. While differences in physical fitness obtained with a significance level (p - value) of 0.006, the result of different physical health of elementary school children stunting and non stunting. Conclusion: There are the differences between learning achievement and physical health of elementary school children stunted and non-stunted in subdistrict of Kartasura Sukoharjo.